The Religious-mythological characters and motifs in the Nart epic Balkars and Karachai - Tanzily M. Khadzhieva (Studia Litterarum)
During their many centuries of history, the Balkars and Karachays have created an extremely rich folklore. The heroic Nart epos occupies the central place in their oral poetic works; it is one of the national versions of the general Caucasus Nartiad. Among the Balkars and Karachays, as well as among other bearers of the Nartiad, the legends consist of a series of large and small cycles. Each cycle is a group of small (in bulk) legends and songs about the appearance of the Nart tribe on earth; about the various stages and events of the epic life of the heroes (birth, heroic childhood, the first exploit, marriage, and the struggle with mythical monsters, with a blood enemy, etc.). In the epos of the Balkars and Karachays, there are original individual songs and legends without parallels in any other national version of the Nartiad. They date basically from the archaic layer of the epic, since there is a predominance of motifs connected to the totemistic, animist, magic, and religious ideas of these peoples who, right up to the 19th century, had some survivals of primitive forms of religion and Christianity, alongside Islam. The Nart epos also reflects the fact that the Balkars and Karachays used to worshiping the sky, fire, water, heavenly lights, animals, trees, stones, etc., and that according to their ideas, each phenomenon and thing had its own Teyri (Tengri).